2015
DOI: 10.1021/acs.jafc.5b03914
|View full text |Cite
|
Sign up to set email alerts
|

Can Coffee Chemical Compounds and Insecticidal Plants Be Harnessed for Control of Major Coffee Pests?

Abstract: Pests and pathogens threaten coffee production worldwide and are difficult to control using conventional methods, such as insecticides. We review the literature on the chemistry of coffee, concentrating on compounds most commonly reported from Coffea arabica and Coffea canephora. Differences in chemistry can distinguish coffee species and varieties, and plants grown under different biogeographic conditions exhibit different chemotypes. A number of chemical groups, such as alkaloids and caffeoylquinic acids, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 136 publications
0
10
0
3
Order By: Relevance
“…For districts, F- would stop drilling the fruit of coffee. Coffee genotypes and species might be different in chemistry whereby some of the chemotypes were shown to be insecticidal (Green et al, 2015). It would be also important to examine whether this pest could adapt to lower pH.…”
Section: Desember 2018mentioning
confidence: 99%
“…For districts, F- would stop drilling the fruit of coffee. Coffee genotypes and species might be different in chemistry whereby some of the chemotypes were shown to be insecticidal (Green et al, 2015). It would be also important to examine whether this pest could adapt to lower pH.…”
Section: Desember 2018mentioning
confidence: 99%
“…The increased susceptibility of mite-infested coffee plants to white mealybugs suggests that red spider mites manipulate plant defences in the same way as other tetranychids do (Alba et al, 2015). Given that O. ilicis is an herbivore more specialized on coffee than the white mealybug, which attacks a wide range of hosts (Roda, Francis, Kairo, Culik, & Peña, 2013), it likely copes better with the specific defences of coffee plants, such as the alkaloid caffeine and the caffeoylquinic acids that act as defensive metabolites to other generalist mealybugs, like Coccus viridis (Green) (Hemiptera: Coccidae) (Fernandes et al, 2011;Green, Davis, Cossé, & Vega, 2015;Magalhães et al, 2010). Although protease inhibitors are not a defence specific to coffee plants, the study by Silva et al (2015) found that O. ilicis can down-regulate their activity in some genotypes of Coffea canephora Pierre, indicating it can potentially manipulate coffee plant defences.…”
Section: Discussionmentioning
confidence: 99%
“…The compounds emitted by C. micans were mostly alcohols, furans, and acetates. Alcohols and acetates are associated with the attraction responses of H. hampei (Mendoza Mora, ; Mathieu et al., ; Cardenas, ; Green et al., ), suggesting that C. micans emits the necessary compounds to attract CBB, but the emission concentration apparently was too low to affect CBB preferences in field conditions (field results were not significant). On the contrary, laboratory results suggested repellence for CBB.…”
Section: Discussionmentioning
confidence: 99%
“…The association between the emission of certain plant volatile compounds and the localization by an insect has been studied in many agrosystems in very specific ways, for both pest and beneficial insects (De Moraes et al., ). Many compounds have been evaluated as vegetable extracts or synthetic compounds for their effect on the control of CBB in coffee plantations (Mendesil et al., ; Dufour et al., ; Jaramillo et al., ; Njihia et al., ; Benavides & Góngora, ; Green et al., ). The results of these studies let us to conclude that it may be a blend of compounds that allows the localization or repulsion of the host, affecting the CBB.…”
Section: Discussionmentioning
confidence: 99%